Exploring the Efficacy of Physiotherapy in Conservative Management of Hallux Valgus: A Scoping Review of Randomized Clinical Trials - Roberto Tedeschi (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. This study evaluates the effectiveness of physiotherapy in treating hallux valgus, a common foot deformity, focusing on various treatment approaches.